Achieving long-term anticorrosion via the inhibition of graphene's electrical activity. Issue 6 (23rd January 2019) - Ding, Jiheng; Zhao, Hongran; Ji, Dong; Xu, Beiyu; Zhao, Xinpeng; Wang, Zhen; Wang, Donglin; Zhou, Qingbo; Yu, Haibin
Abstract : Novel B-doped functionalized graphene: an excellent filler for enhancing the long-term barrier properties of polyurethane coatings. Abstract : Due to its remarkable impermeability to gases, vapours, and liquids, graphene (G) is used as an excellent coating for metal protection. However, due to its high conductivity, recent studies have reported that G fails to prevent metal corrosion under long-term air exposure. Here, we obtained B-doped graphene (BG) and N-doped graphene (NG) with electron donating/withdrawing elements and then used them to modify the waterborne polyurethane (PU) resin. Our work reveals that embedding BG into a PU matrix greatly improves anticorrosion performance. The results revealed that graphene (BG) doped with electron accepting dopants exhibits a long-term corrosion resistance based on the suppression of galvanic corrosion, while graphene (NG) doped with electron donating dopants exhibits corrosion promotion due to its enhanced conductivity. Typically, the impedance modulus of BG/PU at Z f=0.01Hz was up to 10 8 Ω cm 2, increasing by approximately three orders of magnitude compared to that of neat PU, G/PU, and NG/PU (∼10 6 Ω cm 2 ) after immersion for 240 h in 3.5 wt% NaCl(aq) . The present investigation provides important future implications for the fabrication of graphene-based anticorrosive coatings with excellent durability.